2010
DOI: 10.1021/es102725n
|View full text |Cite
|
Sign up to set email alerts
|

Tetracycline Resistance Genes Persist at Aquaculture Farms in the Absence of Selection Pressure

Abstract: The prophylactic and therapeutic use of tetracyclines in aquaculture has been shown to contribute to the spread of tetracycline resistance in the environment. In this work, the prevalence of four different tetracycline-resistance genes, tetA, tetC, tetH, and tetM, in sediments from four aquaculture farms and their surroundings in the Baltic Sea was monitored by quantitative polymerase chain reaction (qPCR). The presence of three additional tetracycline-resistance genes (tetE, tetG, and tetW) was studied qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
155
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 275 publications
(172 citation statements)
references
References 37 publications
8
155
2
Order By: Relevance
“…Tetracycline-resistance genes are found even in small farms which rarely use antibacterials. The copy numbers of tetA, tetC, tetH, and tetM genes (tetR reported by Seyfried et al, (2010)) remain elevated at farms over the surveillance period of four years in the absence of any selection pressure from tetracycline or even other antibacterials (Schmitt & Römbke, 2008;Tamminen et al, 2010). The continued introduction of tetracycline-resistant organisms from the hatchery to the stream, even after a significant time period had elapsed since the use of antibacterials, indicates the presence of reservoirs of organisms or unknown sources of resistance (Stachowiak et al, 2010) as well as other aquatic bacteria, and also illustrates that these bacteria can act as reservoirs of resistance genes that can be further disseminated.…”
Section: Resistance Of Aquatic Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Tetracycline-resistance genes are found even in small farms which rarely use antibacterials. The copy numbers of tetA, tetC, tetH, and tetM genes (tetR reported by Seyfried et al, (2010)) remain elevated at farms over the surveillance period of four years in the absence of any selection pressure from tetracycline or even other antibacterials (Schmitt & Römbke, 2008;Tamminen et al, 2010). The continued introduction of tetracycline-resistant organisms from the hatchery to the stream, even after a significant time period had elapsed since the use of antibacterials, indicates the presence of reservoirs of organisms or unknown sources of resistance (Stachowiak et al, 2010) as well as other aquatic bacteria, and also illustrates that these bacteria can act as reservoirs of resistance genes that can be further disseminated.…”
Section: Resistance Of Aquatic Bacteriamentioning
confidence: 99%
“…The presence of feed residue in the aquatic system would have an important effect for the generation and maintenance of the drug resistance of bacteria in sediment (Yu et al, 2009). These results call for the development of better management strategies for fish farming so as to prevent the emergence of resistant gene pools in the sediments of aquaculture facilities, and to promote the disappearance of established resistant gene pools (Tamminen et al, 2010). Principles for the prudent use of antibacterials should be developed and awareness of the problem of antibacterial resistance should be raised by informing the public (FAO, 2005).…”
Section: Resistance Of Aquatic Bacteriamentioning
confidence: 99%
“…Use of antibiotics in humans and animals could also lead to development and spread of antibiotic-resistant bacteria (ARB) and antibiotic resistance genes (ARGs) in the environment (Pruden et al, 2006;Tao et al, 2010;Su et al, 2012). Therefore, antibiotics and ARGs have been regarded as emerging environmental contaminants and detected in diverse environmental compartments (Tamminen et al, 2010;Su et al, 2012;Cheng et al, 2013;Coleman et al, 2013). It is found that ARGs can be disseminated among bacteria via vertical and horizontal gene transfer, and distributed from human and animal sources to receiving environment .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported wide detection of various antibiotics and ARGs in effluent and sludge from wastewater treatment plants (WWTPs), which could be a major cause for the ubiquitous occurrence of antibiotics and ARGs in various environmental compartments (Pruden et al, 2006;Durham et al, 2010;Li and Zhang, 2010;Tamminen et al, 2011;Gao et al, 2012;Jia et al, 2012;Su et al, 2012;Cheng et al, 2013;Coleman et al, 2013;Zhou et al, 2013). Therefore, a better wastewater treatment technology is needed for removing antibiotics and ARGs.…”
Section: Introductionmentioning
confidence: 99%